2016
DOI: 10.3847/0004-637x/820/2/117
|View full text |Cite
|
Sign up to set email alerts
|

On the Formation of Amide Polymers via Carbonyl–amino Group Linkages in Energetically Processed Ices of Astrophysical Relevance

Abstract: We report on the formation of organic amide polymers via carbonyl-amino group linkages in carbon monoxide and ammonia bearing energetically processed ices of astrophysical relevance. The first group comprises molecules with one carboxyl group and an increasing number of amine moieties starting with formamide (45 u), urea (60 u), and hydrazine carboxamide (75 u). The second group consists of species with two carboxyl (58 u) and up to three amine groups (73 u, 88 u, and 103 u). The formation and polymerization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 100 publications
(114 reference statements)
1
13
0
Order By: Relevance
“…These findings allow speculation about the formation and presence of peptide bonds toward organic molecules in astrophysically relevant ices. Förstel et al (2016b) reported the results of polyamide formation in irradiated ice mixtures of carbon monoxide (CO) with ammonia (NH 3 ). Furthermore, Halfen et al (2011) predicted an abiotic formation for polypeptide under interstellar conditions similar to the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings allow speculation about the formation and presence of peptide bonds toward organic molecules in astrophysically relevant ices. Förstel et al (2016b) reported the results of polyamide formation in irradiated ice mixtures of carbon monoxide (CO) with ammonia (NH 3 ). Furthermore, Halfen et al (2011) predicted an abiotic formation for polypeptide under interstellar conditions similar to the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This ice growth was monitored online and in situ via an interference pattern of the HeNe laser (λ=632.8 nm; CVI Melles-Griot; 25-LHP-230) reflected from the silver wafer and the ice surface. The recorded fringes translate into an ice thickness via Equation (1), which defines the thickness (d) of an ice and the dependence on the number of interference fringes (m), the laser wavelength (λ), and the angle of incidence of the laser beam (θ = 4°): (Turner et al 2015;Förstel et al 2016bFörstel et al , 2016cTsegaw et al 2017…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Dedicated laboratory simulation studies mimicking the processing of interstellar ice analog samples containing, for instance, ammonia (NH 3 ), carbon dioxide (CO 2 ), and carbon monoxide (CO) verified peptide bond formation upon exposure of these ices to ionizing radiation. 1,5,6 Surprisingly, the phosphorus peptide moiety (-CO-PH-) as an † Electronic supplementary information (ESI) available. See…”
mentioning
confidence: 99%
“…Recent experiments in carbon monoxide-methane, 21 carbon monoxide-ammonia, 6 and carbon monoxide-methanol ices 22 also demonstrate that suprathermal hydrogen atoms react with carbon monoxide forming the formyl radical (HCO). If the formyl radical (HCO) has a favorable recombination geometry with the phosphino radical (PH 2 ), both radicals can recombine without barrier leading to the formation of HCOPH 2 (III) reaction (7) as confirmed by calculations (Table S5 and Fig.…”
mentioning
confidence: 99%